2020
DOI: 10.3390/agriculture10070287
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Factors Influencing Youth Involvement in Horticulture Agribusiness in Tanzania: A Case Study of Njombe Region

Abstract: Involvement of youth in horticulture agribusiness has become a vital approach to create employment opportunities among the youth in Tanzania. This study aimed at examining the extent of youth participation and factors influencing youth involvement in horticulture agribusiness with a focus on innovations in post-harvest management (PHM). Data were collected from a sample of 576 male and female youth in Njombe region using a multi-stage random sampling technique. Data were analyzed using an ordered logit model a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 19 publications
8
27
0
Order By: Relevance
“…One arm of the literature argues that youth engagement in nonfarm enterprises drives rural development (see Alemu & Adesina, 2017), whereas the other arm argues that youth entrepreneurship in agriculture (agripreneurship) is critical to the development of the local economies of youth through improved income as well as to national development through reduction in unemployment, increase in GDP and improvement in food and nutrition security. The benefits of youth entrepreneurship have led to a heightened interest of academic researchers in ascertaining the drivers of youth agripreneurship (e.g., Adegboye & Iweriebor, 2018; Coker et al, 2017; Magagula & Tsvakirai, 2020; Ng'atigwa et al, 2020; Nwibo et al, 2016; Ogunmodede et al, 2020). These authors highlight that the key factors that drive youth participation in agriculture include education, income levels, household size, access to credit, good perception of agriculture, income levels, and agribusiness training.…”
Section: Review Of Related Literaturementioning
confidence: 99%
“…One arm of the literature argues that youth engagement in nonfarm enterprises drives rural development (see Alemu & Adesina, 2017), whereas the other arm argues that youth entrepreneurship in agriculture (agripreneurship) is critical to the development of the local economies of youth through improved income as well as to national development through reduction in unemployment, increase in GDP and improvement in food and nutrition security. The benefits of youth entrepreneurship have led to a heightened interest of academic researchers in ascertaining the drivers of youth agripreneurship (e.g., Adegboye & Iweriebor, 2018; Coker et al, 2017; Magagula & Tsvakirai, 2020; Ng'atigwa et al, 2020; Nwibo et al, 2016; Ogunmodede et al, 2020). These authors highlight that the key factors that drive youth participation in agriculture include education, income levels, household size, access to credit, good perception of agriculture, income levels, and agribusiness training.…”
Section: Review Of Related Literaturementioning
confidence: 99%
“…This is due to the employment potential of the agricultural sector given that this sector employs nearly 80 percent of the Beninese population ( Adjimoti, 2018 ). To this end, several studies in different countries have examined the willingness of youth to participate in agricultural training programs, pursue agriculture in school or pursue agribusiness as well as the drivers of youth participation in agriculture and agribusiness ( Adeyanju et al., 2021 ; Haruna et al., 2019 ; Magagula and Tsvakirai, 2020 ; Ng'atigwa et al., 2020 ; Twumasi et al., 2019 ). However, there is limited information on drivers of youth choices of different agripreneurship activities as well as their crop production decisions in Benin.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Adams, Johanson and Razmara (2013) found that only 39% of self-employed FDC graduates were partly involved in farming. More recently Ng'atigwa et al (2020) found that the youth who completed primary school education are more likely to be involved in horticulture agribusiness by about 9.7 times (odds = 9.7) compared with the youth who have a high level of education.…”
Section: Introductionmentioning
confidence: 99%